A Comparison Between Schmidt Rebound Hammer Test and Point Load Index Test (IS50) for the Effectiveness in Estimating the Unconfined Compressive Strength of Intact Rock- A Case Study with respect to Limestone of Early Eocene Nammal Formation, Central Salt: A Comparison Between Schmidt Rebound Hammer Test and Point Load Index Test (IS50) for the Effectiveness in Estimating the Unconfined Compressive Strength of Intact Rock- A Case Study with respect to Limestone of Early Eocene Nammal Formation, Central Salt Range, Pakistan - zahoor, Aun; Azhar, Muhammad Usman; Saif Ur Rehman; shehzad, Farrukh Rahim (International Journal of Economic and Environmental Geology, 2019)
In a bid to find some possible relation of Unconfined Compressive Strength (UCS) with relatively simple laboratory tests like Point Load Test (PLT) and Schmidt Rebound Hammer Test (SRHT), some 50 core samples of Middle Eocene Nammal formation from Central Salt Range in Pakistan were collected and subjected to these test methods as per respective test standards of International Society of Rock Mechanics (ISRM). The values of SRHT and PLT were separately compared to the respective values of UCS so as to find the linear relations. On the basis of the R2 value of Regression Analysis, it has been found that a strong correlation with a high degree of accuracy exists between PLT and UCS while the degree of accuracy between SRHT and UCS was found to be low.